The Effect of Cash Flow and CSR Moderated by Corporate Governance - Wardana, Nofrizal Bagas; Mutyarawati, Herlita; Purwidyasari, Scholastica Meillia; Lestari, Henny Setyo; Leon, Farah Margaretha (Jurnal Keuangan dan Perbankan, 2023)
This study analyzes and examines the effect that cash flow has on financial distress and corporate social responsibility through moderation by the role of corporate governance. The sample of companies applied is manufacturing companies in Indonesia and listed on the Indonesia Stock Exchange with the period 2019-2021. The samples that fit the criteria were found to be 44 companies. The data obtained through purposive sampling and using secondary data from the annual report published by each company. The results of this study indicate that financial distress t-1 has a positive effect on financial distress significantly. corporate social responsibility does not affect financial distress. Corporate governance has a positive effect on financial distress significantly. Cash flow has a negative and significant effect on financial distress. Leverage has a negative and significant effect on financial distress. Asset tangibility does not affect financial distress. Corporate governance moderates the effect of corporate social responsibility on financial distress.DOI: 10.26905/jkdp.v27i4.10685